Removal of Safranin-T and Toluidine from Water through Gum Arabic/Acrylamide Hydrogel - Jabeen, Salma; Alam, Sultan; Shah, Luqman Ali; Zahoor, Muhammad; Rahman, Najeeb Ur; Khan, Farhat Ali; Ullah, Riaz; Ali, Essam A.; Murthy, H. C. Ananda; Sohail, Aamir (Adsorption science & technology, 2022)
Hydrogels as “smart sorbents” for wastewater treatment have attracted much attention due to their facile fabrication, rapid regeneration, environment friendly nature, and strong interaction with pollutants. In this study, gum arabic/acrylamide (GA/AM) hydrogel was developed via the free radical polymerization method by employing acrylamide (AM) (monomer), gum arabic (GA) (grafting backbone), N,N-methylenebisacrylamide (MBA) (chemical crosslinker), and tetramethylethylenediamine (TEMED) (accelerator). The fabricated adsorbent was characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, and surface area analyzer. The adsorption properties of the subject hydrogel were explored against cationic safranin and toluidine dyes in aqueous media. The point of zero charge (PZC) for the GA/AM sorbent was found to be pHPZC=7.1 whereas maximum sorption occurred at pH 11. Different kinetic and isotherm models were applied to evaluate the adsorption mechanism and estimate values of different adsorption parameters. The adsorption isotherm and kinetics were better explained by the Langmuir isotherm and pseudo-second-order kinetic model whereas the adsorption thermodynamics depicted the endothermic, spontaneous, and favorable nature of the process. The adsorbent was regenerated with acetone and reused for the selected dyes for many cycles. After the 5th cycle, the hydrogel retained safranin/toluidine removal capacity≥60% which pointed toward the reusability of the prepared adsorbent for cycles without appreciable reduction in its adsorption capacity. Hence, the GA/AM sorbent can be applied as an alternative of activated carbon to treat dye-contaminated waters.